Comparison of Cephalometric Changes on Skeletodental Structures by the Mini-Maxillary Protraction Appliance and Delaire Type Face Mask - Zahir Altuğ; Hatice Gökalp; Ayşegül Dalkıran (Galenos Yayinevi, 2007)
Objective of present study is to compare the cephalometric changes that occurwith the Mini-Maxillary Protractor and Delaire type face mask therapies for Class III malocclusion. This study included two treatment and one control group. The mean age was 11.55 years in the Mini-Maxillary Protractor group, 11.28 years in the Delaire type face mask group and 10.50 years in the Control group. The mean treatment time was 0.67 months. Pre-treatment (T1) and post-treatment (T2) lateral cephalograms of 43 patients were analyzed by an x-y coordinate system and structural superimpositions. Differences between the T1 and T2 values were analyzed with paired t-tests. The source of the difference between the groups was analyzed by variant analysis and Duncan test. It was found that statistically significant anterior movement of the maxilla occurred in both the Mini-Maxillary Protractor and Delaire type face mask groups. The mandible rotated clockwise with mild decreases in SNB and a significant downward movement at the mandibular plane angle. Linear measurements according to the x-y coordinate system demonstrated that the correction was due more to the maxilla than the mandible. Soft tissue changes included the nose and upper lip moving forward. Improvement of Class III relationship in both groups occurs by a combination of skeletal and dental changes.